Seguimento de crianças com desnutrição moderada ou grave em população periférica (Brasil) Follow up of children with moderate or severe malnutrition in an outlying urban population (Brazil) - Nilson M. Carvalho; Elsa R.J. Giugliani; Cristina F. Seffrin; Rosane M. Hartmann (Universidade de São Paulo, 1992)
Com o objetivo de avaliar o estado nutricional de crianças de uma população urbana periférica de Porto Alegre, RS (Brasil) que apresentaram quadro de desnutrição moderada ou grave antes dos 5 anos de idade, 61 famílias foram procuradas após 2 a 4 anos de uma avaliação inicial. Das 39 crianças localizadas, 4 (10,3%) foram a óbito e 22 (56,4%) apresentaram um incremento na relação peso/idade maior que 10%. Entre as 35 crianças sobreviventes, 29 (82,3%) apresentavam algum grau de desnutrição (peso/idade < 90% do padrão), 25 (71,4%) tinham baixa estatura (altura/idade < 95% do padrão) e 5 (14,3%) possuíam pouco peso para a altura < 90% do padrão). Os irmãos menores de 5 anos de idade apresentaram estado nutricional semelhante ao das crianças reavaliadas. Os fatores que mostraram alguma associação com um melhor estado nutricional (incremento maior que 10% na relação peso/idade no período do seguimento e/ou altura/idade ou peso/altura adequados na segunda avaliação) foram: história de pelo menos uma hospitalização entre a primeira e a segunda avaliação, detecção da desnutrição até os 6 meses de idade e mãe alfabetizada. Os programas de suplementação alimentar e/ou reabilitação nutricional disponíveis na comunidade não influíram na melhoria do estado nutricional, tanto das crianças-alvo como de seus irmãos. Concluiu-se pela necessidade de uma abordagem mais eficaz das famílias que apresentam um alto risco para desnutrição e morbimortalidade infantil. What happens to children who develop moderate or severe malnutrition? What is done for them? Keeping in mind these questions, the present research was undertaken with the following objectives: to assess the nutritional status of children who develop moderate or severe malnutrition before the age of 5 years, after a period from 2 to 4 years after diagnosis; to assess the nutritional status of the under 5-year old siblings of these children; to study the influence of nutritional programs available in the community for the improvement of the nutritional status of the malnourished children; and to identify factors interfering with nutrition of these children during the study period. After a period of 2 to 4 years from the time of diagnosis of moderate or severe malnutrition the authors tried to locate the families of 61 malnourished children of Porto Alegre, RS (Brazil). The mothers their substitutes were interviewed and the children and siblings under 5 years of age were weighed and measured. Thirty-nine children were located. Of these, 4 (10%) died and 22 (56%) presented an increase of at least 10% in weight for age. Of the 35 children who survived, 29 (82%) still presented some degree of malnutrition (weight/age < 90% of the standard), 25 (71%) were stunted (height/age < 95%), and 5 (14%) were wasted (weight/height < 90%). The nutritional status of the 5-year old siblings was similar to that of the malnourished children. The factors showing some association with better nutrition (an increase in weight/age of 10% or more during the study period and/or adequate height/age or weight/height) were: history of at least one hospitalization during follow-up, early detection of malnutrition (before the age of 6 months), and literate mothers. The nutritional programs available in the community did not show any influence on the nutritional status of the malnourished children and their siblings. The present study shows that a more efficient intervention is necessary in the families who are at higher risk for infant morbimortality.